Assessment of bisphenol-related knowledge and awareness among healthcare professionals: a cross-sectional analysis from Türkiye - Aslan, Ekrem; Kaplan, Betül (Frontiers in Public Health, 2025)
BackgroundA class of endocrine-disrupting chemicals with numerous industrial uses and proven harmful health effects are bisphenols, especially bisphenol A (BPA). These substances pose serious exposure risks in healthcare settings because they are widely found in consumer goods, food containers, and medical equipment. Even though there is growing evidence that exposure to bisphenols can cause metabolic, reproductive, and cardiovascular problems, little is known about these environmental toxins by medical professionals. One major obstacle to efficient risk assessment, patient counseling, and occupational safety implementation in clinical settings is the lack of awareness among frontline healthcare workers.MethodsThe healthcare professionals at Gaziantep University Şahinbey Research and Training Hospital participated in this descriptive cross-sectional study from April 15 to September 15, 2024. 397 healthcare professionals, including physicians, nurses, midwives, and health technicians, participated in standardized in-person interviews using a validated 13-item bisphenol knowledge assessment questionnaire. The data analysis was conducted using SPSS 25.0 software and included descriptive statistics, independent samples t-tests, one-way ANOVA, chi-square tests, Spearman correlation analysis, and CHAID decision tree analysis.ResultsA critically low level of awareness was indicated by the fact that only 23.7% of participants reported having previously encountered bisphenols. With a mean knowledge score of 3.90 ± 3.48 out of 13 possible points, 82.6% of healthcare professionals were classified as having inadequate knowledge (p < 0.001). A significant difference in knowledge was observed based on professional title (physicians scored the highest, p = 0.015), marital status (married vs. single: 4.26 ± 3.57 vs. 3.39 ± 3.30, p = 0.014), and professional experience (6–10 years vs. 0–5 years: 4.29 ± 3.48 vs. 3.30 ± 3.15, p = 0.049). A positive correlation was observed between age and knowledge levels (r = 0.133, p = 0.008).ConclusionThe vast majority of Turkish healthcare professionals do not fully comprehend the sources of exposure, the health risks, or the precautions that should be taken about bisphenols, according to this study. These findings indicate that comprehensive educational interventions and policy reforms are urgently required to enhance environmental health literacy in healthcare settings.